Conceptual Design of Electromechanical Actuation Systems for Large-Sized Directional Control Valves - Tobias Vonderbank; Katharina Schmitz (Actuators, 2021)
Increasing performance in modern hydraulics is achieved by a close investigation of possible enhancements of its components. Prior research has pointed out that electromechanical actuators can form suitable alternatives to hydraulically piloted control systems. Since the requirements at these actuation systems depend on the operating conditions of the system, each actuator can be optimized to the respective hydraulic system. Considering that many different conceptual designs are suitable, the phase of conceptual design plays a decisive role during the design process. Therefore, this paper focuses on the process of developing new conceptual designs for electromechanical valve actuation systems using the method of function structures. Aiming to identify special design features, which need to be considered during the design process of electromechanical actuation systems, an exemplary actuator was designed based on the derived function structure. To highlight the potential of function structures for the development of new electromechanical valve actuation systems, two principal concepts, which allow the reduction of the necessary forces, have been developed by extending the function structure. These concepts have been experimentally investigated to identify their advantages and disadvantages.